2023
DOI: 10.4155/fmc-2022-0309
|View full text |Cite
|
Sign up to set email alerts
|

Structure Modification: a Successful Tool for Prodrug Design

Abstract: Prodrug strategy is critical for innovative drug development. Structural modification is the most straightforward and effective method to develop prodrugs. Improving drug defects and optimizing the physical and chemical properties of a drug, such as lipophilicity and water solubility, changing the way of administration can be achieved through specific structural modification. Designing prodrugs by linking microenvironment-responsive groups to the prototype drugs is of great help in enhancing drug targeting. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Given the vulnerability of drug structure, the conventional structural modification strategies of drugs were introduced in the review ( Cheng et al, 2023 ). Here, we mainly summarized the protection strategies of nanotechnology for drug stability, including the encapsulation of drugs by nanomaterials, improving surface characteristics, and modifying nanomaterials.…”
Section: Current Strategies For Improving the Properties Of Nanotechn...mentioning
confidence: 99%
“…Given the vulnerability of drug structure, the conventional structural modification strategies of drugs were introduced in the review ( Cheng et al, 2023 ). Here, we mainly summarized the protection strategies of nanotechnology for drug stability, including the encapsulation of drugs by nanomaterials, improving surface characteristics, and modifying nanomaterials.…”
Section: Current Strategies For Improving the Properties Of Nanotechn...mentioning
confidence: 99%
“…The carbamate strategy, which involves chemically modifying the structure of the drug itself to improve the bioavailability of the drug, is routinely used to improve the phase II metabolic stability of some flavonoids, such as resveratrol and baicalein. 31–34 Due to the effect of the electron-donating groups on the carbamate bond and the esterase inhibitory activity of the carbamates, carbamates have good stability and can avoid being broken down before entering the body. 35 Besides, structure–activity relationship analysis revealed that mono-substitution at the 3-OH group of ICT could improve the cytotoxicity of cancer cells.…”
Section: Introductionmentioning
confidence: 99%